Health quality of retired Royal New Zealand Navy personnel: A cross-sectional analysis - Doug King; Patria A Hume; Trevor N Clark; Conor Gissane (Archives of Community Medicine and Public Health - Peertechz Publications, 2021)
Purpose: To characterise the current health quality of retired Royal New Zealand Navy (RNZN) personnel. Methods: A Cross-sectional analysis of self-reported survey data was conducted. A total of 300 retired RNZN personnel completed a Health-Related Quality of Life (HRQOL) survey on-line using the SF-36v2 to assess physical and mental health domains. The Physical Component Summary [PCS] combined Physical Function (PF), Role Physical (RP), Bodily Pain (BP) and General Health (GH) subscales. The Mental Component Summary [MCS] combined Vitality (VT), Social Functioning (SF), Role Emotional (RE) and Mental Health (MH) subscales. Analysis by age, gender, ethnicity, and rank were conducted for the subscale results. Comparisons of the RNZN cohort with the 1998 US National and New Zealand 2006-2007 health surveys were made.  Results: New Zealand Europeans (NZE) recorded a higher mean RP and PCS than New Zealand Māori (NZM) (RP: 66.9 vs. 54.9; t(46)=-2.2; p=0.0294; d=0.50; PCS: 68.9 vs. 65.7; t(46)=-2.3; p=0.0267; d=0.47). Senior Rates recorded a higher MH (69.5 vs. 66.2; t(19)=-1.1; p=0.0568; d=0.35) but a lower PCS (65.0 vs. 65.6; t(19)=0.6;p=0.0681 d=0.07) and MCS (59.2 vs. 59.4; t(19)=-1.4; p=0.0865; d=0.46) than Officers. Compared with the New Zealand 2006-2007 health survey, the retired RNZN cohort had a lower RP (58.0 vs. 85.7; d=1.14), BP (42.6 vs. 75.3; d=1.51), SF (59.8 vs. 88.4; d=1.85) and MH (68.5 vs. 82.3; d=1.28). Conclusion: The lower HRQOL subscales results (especially BP) for retired RNZN personnel compared to the general population and other service personnel indicates a need for more research to understand the potential reasons for these findings. The effects of the lifestyle and training requirements combined with the entry selection of healthy people into the navy may have impacted on the results reported in this survey.